Evaluation of the antigenic value of recombinant Toxoplasma gondii HSP20 to detect specific immunoglobulin G antibodies in Toxoplasma infected humans - Cóceres, Verónica Mabel (2010)
Recombinant Toxoplasma gondii small heat shock protein HSP20, surface antigen SAG1 and dense granule GRA7 were analyzed by IgG-ELISA with serum samples of Toxoplasma infected humans grouped as I (IgG+, IgM+), II (IgG+, IgM-) and III (IgG-, IgM-). rHSP20 reacted against 80% and 62.5% of serum samples from groups I and II, respectively. rSAG1 was recognized by 85% of the samples from group I and 70.8% from group II, whereas rGRA7 was recognized by 85% and 66.6% of the serum samples from groups I and II, respectively. When a combination of two or three recombinant antigens was used, the sensitivity values improved to 85-95% for group I and 87.5-91.7% for group II. All combinations tested produced similar reactivity profiles. None of the recombinant proteins reacted against group III serum samples. In conclusion, we demonstrated that T. gondii HSP20 elicits an important B-cell response during human infection, and could be suitable for the development of serodiagnosis tools.